Die Ritualkiste als Methode für einen kompetenzorientierten Unterricht zum Thema Übergangsrituale - Dobi, Celina (Zeitschrift für Religionskunde, 2015)
This contribution discusses a unit plan aimed at students aged 10 to 15, on the subject of “rites of passage”. The unit mobilizes a new teaching tool, the “ritual box”, which this contribution will analyze.